Pengaruh Pembelajaran Jarak Jauh Kelas 7.3 terhadap Prestasi Belajar pada Mata Pelajaran IPS Di SMP Islam Al-Ikhlas Bekasi - Merry Sekar Aliffia (Jurnal Syntax Transformation, 2021)
This study aims to reveal the effect of Distance Learning (X) on Social Studies Subject Learning Achievement (Y). This research method is descriptive quantitative. In determining the sample used is a saturated sample and the sample used for this study as many as 29 people. The conclusions from the results of this study reveal: (1) Distance learning and learning achievement are normally distributed in distance education of 0.222 and sig. (2-talied) of 0.001 > 0.05, Ho is accepted. Thus the distance learning data is normally distributed. While the learning achievement score is 0.247 and sig. (2-talied) of 0.000 > 0.05, Ho is accepted. (2) The effect of distance learning on learning achievement in social studies subjects is a positive influence. The results of this study using the SPSS 26.0 program using the regression equation: Y = 96.689 + -0.165 X. From the analysis results obtained thit = 6.578 and p-value = 0.351> 0.05 or Ho is rejected. (3) Based on the test results, the correlation coefficient value using the Summery model table (R²) is 0.180, which means the contribution of variance given by the X variable to Y. While the coefficient of determination from the table, namely R Square = 0.032, which contains that 03.2 % of learning achievement variables. From the results of the calculation of the GAP above that distance learning can provide a very rapid achievement of student achievement in school or outside school. And independent learning can be organized systematically in presenting learning materials, providing guidance to students, and supervision for the success of learning.